The transition from High school to university: vocational values of high school students with preference for the study of social work degree - Franco, Vicente Hernández (Miscelánea Comillas, 2014)
In connection with the «Observatory of Interests, Vocational Values and Preferential Studies of Secondary and High-school Students» (Orion Project) we set as main objective to explore the vocational profile of 12th Grade students that have as preferential option —between their four principal alternatives— to study the degree of Social Work. We also aim to analyze the ç connection between the supply and demand of vacancies for such certification in the Community of Madrid, as well as to examine the level of employability of graduates on this degree. A total of 4775 surveyed from 12th grade answered to the amount of Orientation quizzes offered in Orion Project Vocational e-Folder. We have quarried aspecific sub-sample composed of 130 students that have as preferential alternative to continue their post-secondary studies in the degree of Social Work after graduating high school.We found out a constant trend in the last 14 years: the supply of vacancies in the degree of Social Work has always been higher than the demand of students. There fore we can conclude that the occupational integration of graduates from Social Work is slightly higher than the average of the rest of university certifications,both in the Community of Madrid and at a national level. We also noted a specific profile of interests and vocational values for 12th Grade students that chose Social Work as their preferential studies. We discovered that their vocational area of preferential interest is «Teaching and Orientation» and the vocational value that mainly distinguish them is «Helping people».All this records might be of great interest for the orientation of high-school studentsthat choose as preferential option to continue their studies in the degree of Social Work.